Phylogeography of the Bradyrhizobium spp. Associated With Peanut, Arachis hypogaea: Fellow Travelers or New Associations? - Bouznif, Besma; Guefrachi, Ibtissem; Rodríguez de la Vega, Ricardo C.; Hungria, Mariangela; Mars, Mohamed; Alunni, Benoit; Shykoff, Jacqui Anne (Frontiers in Microbiology, 2019)
Legume plants have colonized almost all terrestrial biotopes. Their ecological success is partly due to the selective advantage provided by their symbiotic association with nitrogen-fixing bacteria called rhizobia, which allow legumes to thrive on marginal lands and nitrogen depleted soils where non-symbiotic plants cannot grow. Additionally, their symbiotic capacities result in a high protein content in their aerial parts and seeds. This interesting nutritional value has led to the domestication and agricultural exploitation of several legumes grown for seeds and/or fodder for human and domestic animal consumption. Several cultivated legume species are thus grown far beyond their natural geographic range. Other legume species have become invasives, spreading into new habitats. The cultivation and establishment of legume species outside of their original range requires either that they are introduced or cultivated along with their original symbiotic partner or that they find an efficient symbiotic partner in their introduced habitat. The peanut, Arachis hypogaea, a native of South America, is now cultivated throughout the world. This species forms root nodules with Bradyrhizobium, but it is unclear whether these came with the seeds from their native range or were acquired locally. Here we propose to investigate the phylogeography of Bradyrhizobium spp. associated with a number of different wild and cultivated legume species from a range of geographical areas, including numerous strains isolated from peanut roots across the areas of peanut cultivation. This will allow us to address the question of whether introduced/cultivated peanuts associate with bacteria from their original geographic range, i.e., were introduced together with their original bacterial symbionts, or whether they acquired their current associations de novo from the bacterial community within the area of introduction. We will base the phylogenetic analysis on sequence data from both housekeeping and core genes and a symbiotic gene (nif). Differences between the phylogenetic signal of symbiotic and non-symbiotic genes could result from horizontal transfer of symbiosis capacity. Thus this study will also allow us to elucidate the processes by which this symbiotic association has evolved within this group of Bradyrhizobium spp.